EFEKTIFITAS AIR KELAPA HIJAU MUDA TERHADAP PENURUNAN TEKANAN DARAH TINGGI PADA LANSIA DI POSYANDU USILA PUSKESMAS PERAK TIMUR SURABAYA - Sari, Ninik Ambar; Sustrami, Dya (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2018)
Hypertension is an increase in blood pressure where the systolic pressure is more than 140 mmHg and diastolic pressure is more than 90 mmHg. The cause of the onset of hypertension can be of age factor. Elderly who suffer from hypertension usually cause interruption of daily activities, so routine treatment is needed in order not to cause complications. Young coconut water contains potassium, magnesium and vitamin C which has benefits to help the body regulate blood pressure, so it can reduce hypertension. The purpose of this study was to determine the effect of young coconut water on the decrease of high blood pressure in the elderly. Experimental Quasy research design with Non-Equivalent Control Group Desaign approach. The population of this study is elderly who are not dependence of hypertension drugs as much as 32 people with the number of samples of 30 respondents selected by Probability Sampling with Simple Random Sampling approach. The independent variable is young coconut water therapy, the dependent variable is the decrease of high blood pressure. Data were collected using questionnaires and observations. Data were analyzed by using Paired t-test and Independent t-test. The results showed that the consumption of young coconut water as much as 250 ml morning and afternoon for 2 weeks in the treatment group can lower systolic blood pressure. The independent t test in the treatment group and the control group obtained the result p = 0.013 (p <a = 0.05). The implication of this study is that young coconut water can lower blood pressure in elderly people with hypertension, so that young coconut water treatment can be used as one of the non-pharmacological alternative to reduce blood pressure.